The MAP Kinase SsKpp2 Is Required for Mating/Filamentation in Sporisorium scitamineum - Deng, Yi Zhen; Zhang, Bin; Chang, Changqing; Wang, Yixu; Lu, Shan; Sun, Shuquan; Zhang, Xiaomeng; Chen, Baoshan; Jiang, Zide (Frontiers in Microbiology, 2018)
In the phytopathogenic fungus Sporisorium scitamineum, sexual mating between two compatible haploid cells and the subsequent formation of dikaryotic hyphae is essential for infection. This process was shown to be commonly regulated by a MAPK and a cAMP/PKA signaling pathway in the corn smut fungus Ustilago maydis but remains largely unknown in S. scitamineum. In this study we identified a conserved putative MAP kinase Kpp2 in S. scitamineum and named it as SsKpp2. The sskpp2 mutant displayed significantly reduced mating/filamentation, which could be partially restored by addition of cAMP or tryptophol, the reported fungal quorum-sensing molecule identified in budding yeast. Sensitivity assay showed that the sskpp2 mutant was hypersensitive towards cell wall stress while not to osmotic or oxidative stress. Transcriptional profiling showed that genes governing S. scitamineum mating or tryptophol biosynthesis were significantly down-regulated in the sskpp2 mutant compared to the WT, under mating condition. Our results demonstrate that the MAP kinase SsKpp2 is required for S. scitamineum mating/filamentation likely through regulating the conserved pheromone signal transduction pathway and tryptophol production.